Filsafat sebagai Fondasi Ilmu dan Pendidikan di Indonesia - Sahdan, Sahdan (Indo-MathEdu Intellectuals Journal, 2026)
Disciplines and educational practices in Indonesia often leave behind philosophical values ​​that should be the foundation of every science in education. This literature study aims to make critical studies related to the existence of philosophy in understanding the foundations of science and education in Indonesia. The data is in the form of a number of books and journals that are relevant to philosophy, science and philosophy of education with thematic analysis which is then analyzed by identifying various related sources and finding conclusions based on these sources. The results in this paper are studies on epistemology, ontology, and axiology the foundations of all contemporary science very important for the advancement of science. Optimization of the follow-up of this study can be carried out with further research in terms of systematic action in education in various regions in Indonesia, both in terms of educational methods and content in educational activities.